Elementos norteadores da relação orientador-orientando: evidências no mestrado acadêmico em ciências contábeis da UFRN - Barbosa, Ilana Inácio da Silva (2019)
This study aims to investigate in the view of orientandos and orientadores the guiding elements of this relation in the dissertation process of the MSc in Accounting Sciences of the Federal University of Rio Grande do Norte. For this, interviews were conducted with 14 orientandos and 8 program leaders. The analyzes of the interviews were carried out through content analysis, with the assistance of ATLAS.ti®. The research approach was qualitative. The results on guideline practice demonstrate convergence in the dyad accounts when reporting unsystematic encounters during the writing of the dissertation. Regarding the competences, the interviewees mentioned those of a technical and behavioral nature. Regarding the behavioral difficulties, the majority of the orientandos and orientadores showed the inexistence of difficulties of this kind. Regarding the behavioral factors that facilitated the orientation, the subjects were informed by their involvement with the theme, their availability, the autonomy of choosing the theme, the supervisor's empathy, zeal, confidence, motivation, patience, independence in work and respect and punctuality as aspects that contributed to the relationship. The advisors cited humility, autonomy, resilience, responsiveness, synergy and determination. Concerning convergences, thematic and methodological issues were reported in pairs. On the divergences, the majority of the orientandos reported those of theoretical and methodological character. For the minority of the advisors, they pointed out the lack of discipline of the orientandos. Regarding the choice of theme, a small asicronia in the speech of the dyad was noticed. About the accounts of the ease with the writing, a tuning was perceived. In relation to the ease with the literature, there were similarities in the binomial speeches, indicating a lack of initial knowledge of the literature during the elaboration of the dissertation. On facilities with the methodology, the pairs reported that they immediately had no domain. Regarding the operational difficulties, some orientandos and orientadores revealed the methodological and thematic ones. On the operational factors facilitating orientation, the methodological, thematic and literary affinity was identified in the dyad's view. With regard to the misunderstanding between the pairs, orientandos and guiding ones revealed the nonexistence of these. On particular problems, there were similarities in the speech of the dyad about some reports of health problems, the profession and the family context. As a suggestion for improvement in orientation the orientandos recommended an alignment of the subject with the supervisor, timely feedback, a rearrangement in orientation, being accessible, understanding the side of the orienting, transparency in the relation of the dyad, the opening of the advisor to new subjects and the good sense of both sides. The advisors suggested an agenda of meetings with the students, the recognition of the orienting profile and the respect of their particularities, a better follow-up of the student from the beginning of the course, the synergy between the peers and the aspects of the research and the stimulation to the critical spirit of the student.